Optimising adolescent health: a comparative study of high-intensity interval training and moderate-intensity continuous training on body composition and cardiovascular fitness in sedentary male youth - Yahat, Huseyin (Frontiers in Sports and Active Living, 2025)
BackgroundExcess body fat and weight are key risk factors for morbidity and mortality, particularly during adolescence. High-Intensity Interval Training (HIIT) and Moderate-Intensity Continuous Training (MICT) are both widely used strategies to improve body composition, yet limited evidence exists comparing their effects among sedentary, normal-weight adolescent males.MethodsThis randomized controlled study aimed to compare the effects of HIIT and MICT on body composition and cardiovascular fitness in sedentary male adolescents. Sixty normal-weight males aged 16–17 years were randomly assigned to one of three groups: HIIT (n = 20), MICT (n = 20), or control (CG; n = 20). The HIIT protocol comprised six 30-second high-intensity running intervals (80%–90% HRmax) interspersed with 90 s of low-intensity walking (50% HRmax), totalling 20 min per session. The MICT protocol involved continuous running at 60%–70% HRmax for 30 min, inclusive of warm-up and cool-down. Both intervention groups trained four times weekly over 8 weeks, while the control group received no intervention. Pre- and post-intervention measurements included body fat percentage, body weight, skinfold thickness, and resting heart rate, analysed using one-way ANOVA with Bonferroni post hoc comparisons. Given its shorter duration and comparable outcomes, HIIT appears time-efficient for school-based delivery in normal-weight adolescent males, addressing a population and setting under-represented in prior trials.ResultsSignificant reductions in body fat were observed in both the HIIT (−6.0%, p < 0.001, ES = 0.97) and MICT (−5.7%, p < 0.001, ES = 0.76) groups, with no meaningful change in the CG (−1.0%, p > 0.05). Both HIIT and MICT groups also demonstrated significant weight loss (−7.45%, p < 0.001), compared to a negligible change in CG (−0.89%, p > 0.05). Skinfold thickness significantly decreased in HIIT (−24.70%, p < 0.001) and MICT (−23.66%, p < 0.001), with minor change in CG (−4.12%, p > 0.05). Resting heart rate improved in HIIT (−9.14%, p < 0.001) and MICT (−7.12%, p < 0.001), whereas the CG experienced a slight increase (+0.026%, p > 0.05).ConclusionsBoth HIIT and MICT are effective for improving body composition and cardiorespiratory fitness in sedentary male adolescents. Given its shorter duration and comparable outcomes, HIIT may be a time-efficient option for integration into school-based physical education